PENGARUH STRUKTUR SINTAKTIS TERHADAP PROSES MORFOLOGIS DALAM STRUKTUR MORFOLOSINTAKTIS BAHASA INDONESIA - Tukiran, D . (Majalah Transformatika, 2009)
The study of morphosyntactic on the use of Indonesia language is the study of significance unit of morphological process that is influenced by the predicative phrase of syntaxtic. The study  on  syntagmatic refers to (1) fixation including  analogy, thematic, topication of constituent, verbal attraction, and (2) condensation. The integrity of affix morpheme with a lexical item in the beginning of predicative phrase  is paradigmatic grammatication. Keyswords : morphosyntactic, syntagmatic, paradigmatic, predicafive phrase.